DNA strand separation during activation of a developmental promoter by the Bacillus subtilis response regulator Spo0A - Rowe-Magnus, Dean A. (The National Academy of Sciences, 1998)
Spo0A is the central regulator of commitment to sporulation in Bacillus subtilis. Spo0A is a member of the response regulator family of proteins and both represses and stimulates transcription from promoters when activated. In vivo Spo0A activation takes place by phosphorylation and in vitro activation can be accomplished by phosphorylation or removal of the N-terminal domain of the protein. We have examined the mechanism of Spo0A stimulation of transcription from the promoter of the spoIIG operon. This operon encodes one of the first compartment specific sigma factors whose appearance regulates sporulation development. When activated Spo0A was incubated with RNA polymerase and a DNA fragment containing the spoIIG promoter, bases between −13 and −3, relative to the start site of transcription, were denatured. Addition of activated Spo0A or RNA polymerase alone did not induce denaturation. Heteroduplex templates that contained the nontemplate sequence of the wild-type promoter on both strands between positions −3 and −13 were efficiently transcribed without activated Spo0A. These data suggest that DNA strand separation is a two-step process and that the activation of Spo0A creates a form that interacts with the polymerase to induce the first of the two steps.